Rational Solutions of the H3 and Q1 Models in the ABS Lattice List - Shi, Y.; Zhang, D. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
In the paper we present rational solutions for the H3 and Q1 models in the Adler-Bobenko-Suris lattice list. These solutions are in Casoratian form and are generated by considering difference equation sets satisfied by the basic Casoratian column vector.